The Ruling On Marriage with The Intention of Divorce (A Jurisprudential Study) (Al-Mukhtar Journal of Legal Science, 2025)
This study included the concept of legitimate marriage that is in accordance with the intent of the Lawgiver from marriage, and the difference between it and similar corrupt marriages, such as temporary marriage and tahlil marriage, and clarified the evidence and sayings of the predecessors on that. This study also dealt with the essence of its subject, which is marriage with the intention of divorce, in terms of: the concept, the ruling, and the sayings and fatwas of the scholars of the predecessors and successors on this marriage, and indicated the opinion that the soul is reassured by and the heart is inclined towards, and is based on strong arguments that are based in their origin on the evidence of the Qur’an and Sunnah, and the objectives of the Lawgiver in legislating marriage. In conclusion, this study dealt with the most important results and recommendations that the researcher reached.
Keywords: A Marriage that has No Permanence; No Stability; No Affection; and no Peace